Impact of Monitoring Land Use Changes to Anticipate Management of Erosion Rates in the Brantas Hulu Watershed - Pratama, Alfyan Amar; Suripin, Suripin; Wulandari, Dyah Ari; Marupa, Ivan (Universitas Diponegoro, 2024)
Land use change in river basins is an important issue for policymakers. In this case, it is essential to carry out comprehensive monitoring for decision-making. Land use monitoring must be carried out continuously so that changes that occur over a certain period can continue to be monitored. In this case, the Brantas Hulu watershed includes Batu City, Malang City, and Malang Regency. This river basin is considered critical due to massive land use changes. This condition directly encourages an increase in sedimentation rate in rivers and reservoirs. This research aims to obtain the results of monitoring land use changes and determine the handling of erosion rates by monitoring land use changes in the Brantas Hulu watershed. The method used to determine the spatial characteristics of soil erosion in the Upper Brantas watershed uses the Universal Soil Losses Equation (USLE) method. The research results show that erosion conditions in the Brantas Hulu watershed are dominated by class I/very light erosion hazards (36.43%). ), class II/light (22.35%), class V/very heavy (16.07%), class III/moderate (13.09%), and class IV/heavy (12.05%). The proposed control measures for erosion sites include structural and non-structural approaches.